Implementation of Cartoon Animation Based Media to Enhance the Learning of Islamic Studies Education at SMK Ar-Rahma Carat Gempol Pasuruan - Ahmad Ainul Yaqin; Ahmad Ma’ruf (Intiqad: Jurnal Agama dan Pendidikan Islam, 2023)
The purpose of this study was to find out how the implementation of cartoon-based media in improving the learning of Islamic religious education at SMK Ar-Rahma Carat Gempol Pasuruan. The type used in this research is descriptive qualitative type, the data sources used are primary data sources and secondary data sources with observation, interview and documentation research methods. The findings of this study are (1) The use of cartoon animation media can attract students' attention and can increase students' interest in teaching and learning activities. (2) The advantages of using cartoon animation media are that it can make students more enthusiastic and interested, and can make students understand the material presented, so that students are motivated to participate in learning activities. (3) The weakness of using this animation media is inadequate facilities such as lack of projectors, so it can hinder the progress of learning activities. (4) The solution to overcome the weaknesses is that before using animation media as learning materials, it would be better if the teacher prepares the material to be taught, the teacher pays attention to the students' sitting position so that it is routinely rolled from front to back and vice versa, so that when the animation video is played, students can see clearly and added with several other projectors. To create a conducive and comfortable atmosphere, and to provide some questions for the students when the learning process is completed.